DISCREPANCIES IN THE PERCEPTION OF CONFLICTS BETWEEN PARENTS AND THEIR CHILDREN DURING ADOLESCENCE - Motrico, Emma; Fuentes, María Jesús; Bersabé, Rosa (Anales de Psicología / Annals of Psychology, 2001)
The aim of this investigation consists in analyzing the conflicts taking place between parents and their children, as well as the discrepancies in the perception of the actual conflicts arising during adolescence. The sample is made of a total of 402 adolescents (200 boys and 202 girls) -with ages between 12 and 17 years- and 258 parents. The results show a low rate of conflict between parents and their children. The children identified the same sources of arguments between their parents and themselves (both mother and father). On the other hand, the analysis of the data obtained concerning children’s perception of conflicts according to the gender of parents and adolescents revealed significant differences in some of the perceived causes of conflict. It was also found that, around certain issues, the older adolescents (15-17 years) have more conflicts with both parents than the younger ones (12–14 years).